THE MOST COMMONLY USED MEDICINES BY MEDICAL STUDENTS FOR SELF-MEDICATION - Pereira, Gabriel de Oliveira; Lima, Helen de (CIPEEX, 2025)
Self-medication is a common and worrying practice, especially among medical students, which involves the use of medications without a prescription. This study aims to identify the drugs most commonly used by these students, with a special focus on psychiatric drugs used for anxiety, depression, and ADHD. The research was conducted through a literature review, covering articles published between 2018 and 2024, and focused on studies conducted in Brazil. Articles related to self-medication in medical students were used as inclusion criteria, and articles that did not mention which drugs were used were excluded. The descriptors used were "Self Medication," "Students," "Medical," and "Psychiatric drugs." The results indicate that the most commonly used drugs include antipyretics, analgesics, benzodiazepines, and selective serotonin reuptake inhibitors, such as fluoxetine and escitalopram. The indiscriminate use of these drugs without a proper medical prescription can pose significant health risks, highlighting the need for educational interventions and targeted public health policies.